Variation conscious assembly fixturing methodologies for the preliminary weld processes of segmented ring structures - Lowth, Stewart (2016)
This project was sponsored by Rolls-Royce, who had an interest in using scientific principles to improve the geometric accuracy (circularity) of large welded annular structures. This project therefore critically examines and models the mechanisms by which manufacturing variation in wedges components stack and propagate to influence the final assembly geometry. The Trent 900 (T900) Front Bearing Housing (FBH) Ring of Vanes (RoV), was used as an illustrative test-piece, so that the typical sources of variation in large annular assemblies could identified. Also examined was the interplay between assembly gaps created by component variation played and the thermal-mechanical distortions of the Preliminary Welding Process (PWP).